The Serum Immunoglobulin E Level: Is There a Relationship With the Clinical Course of the Gianotti-Crosti Syndrome? - Bassi, Andrea; Pedaci, Fausto; Oranges, Teresa; Azzari, Chiara; Galli, Luisa; Ricci, Silvia; Filippeschi, Cesare; Venturini, Elisabetta (Frontiers in Pediatrics, 2021)
BACKGROUND: Gianotti Crosti syndrome (GCS) is a self-healing condition with a spontaneous resolution in 2-6 weeks but, even if rarely, recurrent episodes have been reported. OBJECTIVE: The aim of this observational study is to investigate serum Immunoglobulin E (IgE) level in children with GCS, evaluating if there is a relationship between IgE level and clinical course of the disease. METHODS: Children with GCS diagnosed at a tertiary care children’s university hospital between June 2018 and November 2019 were prospectively enrolled. Demographic, clinical and hematochemical data of children investigated were collected. In particular, IgE level were investigated at symptoms onset and, if available, at the following blood tests. Patients were divided in two groups on the bases of the clinical course: children with a chronic relapsing course and children who did not present any relapse. RESULTS: Among 29 patients enrolled in this study, 14 (48.3%) children had a chronic relapsing course and 15 (51.7%) did not present any relapse. A statistically significant difference was present considering the length of the disease: 210 days (IQR: 161.25-255) for patients with a chronic relapsing course compared to 40 days (IQR: 30-75) for the other group (p<0.0001). About the median IgE level in the two groups, a value about ten time higher was found in children with chronic course compared to the other group (1144 vs 116 U/mL) with a statistically significant difference (p<0.0001). CONCLUSION: Despite the study limitations, a significant correlation between higher IgE levels and chronic-relapsing course of the GCS can be assumed.